2018
DOI: 10.1287/inte.2017.0937
|View full text |Cite
|
Sign up to set email alerts
|

Helping Merchants to Assess the Profitability of Deal-of-the-Day Promotions

Abstract: The ability to calculate and understand the profitability of deal-of-the-day promotions (DoDs) is of vital importance for merchants. It is also challenging because it requires these merchants to consider long-term, cross-selling, and cannibalization effects and select an appropriate discount for the promotion. The authors develop and implement a model as a free online calculator ( http://www.coupon-calculator.com ) to help merchants to determine the profit they can generate from these promotions. This calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Reiner and Skiera [30] found that all merchants achieved a positive profit. However, this finding is driven mainly by long-term profits; short-term profits were only slightly positive.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Reiner and Skiera [30] found that all merchants achieved a positive profit. However, this finding is driven mainly by long-term profits; short-term profits were only slightly positive.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Lastly, we explore whether o not there is a state of the economy effect on DOD offerings. In summary, we explore how DOD varies across multiple product categories, during festival and non-festival seasons and with the state of the economy (Boon et al, 2015 ; Gafni et al, 2014 ; Liu and Sutanto, 2012; Parsons et al, 2014 ; Reiner and Skiera, 2018 ). Therefore, we define our research questions as:Is there a significant difference in savings made by customers by purchasing different discounted DOD value offerings, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Marketers use several promotional schemes to lure buyers in online environments to make purchases and increase their purchase frequency and to establish loyalty relationships with them (Rocha et al , 2019; Sarkar et al , 2019; Yadav and Rahman, 2018). Deal of the Day (DOD) is one such promotional scheme adopted by online retailers, whereby products are offered on sale for a particular period of time (usually 24–36 h) (Reiner and Skiera, 2018). DOD helps the online retailers to boost the daily footfall on their websites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation